Design of chainless bicycle transmission system using four linkages mechanism. Issue 1 (December 2020) - Kartawidjaja, Vincent; Purna Irawan, Agustinus; Halim, Agus; Abdullah, M. Z.; Ekarista, Maria; Dimas Baskara, Gregorius
Abstract: Bicycle is one of the most popular transportations in the world because it is emission-free and can be used by everyone. Bicycle is always evolving in accordance with the latest technology. Various designs have emerged to change the shape of the bicycle to the present. Design is important in making new concepts to overcome existing problems. The design of a bicycle transmission system without a chain intends to overcome the problem of maintenance needs of a chain-equipped bicycle. The design of the bicycle chain transmission system was changed using a four linkages mechanism. Two types of models were made using the same principle. These two types of bicycle system designs use a four linkages connecting mechanism. The system motion simulation is created using Fusion 360. Motion simulation of this system shows that bicycle transmission without chain works properly. The two types of designs will be compared based on the force needed to move the bike and the results of the simulation.